Experience from a medical college in Saudi Arabia on undergraduate curriculum management and delivery during COVID-19 pandemic - Mona Soliman; Saleh Aldhaheri; Khalid Fouda Neel (Wolters Kluwer Medknow Publications, 2021)
Coronavirus disease 2019 (COVID-19) was declared a pandemic by the World Health Organization on March 11, 2020. In response to the pandemic, the Kingdom of Saudi Arabia's Ministry of Education announced the suspension of educational activities. The pandemic has challenged universities worldwide to provide education virtually as an immediate response to prolonged lockdown periods. This article highlights the College of Medicine's experience at King Saud University, Saudi Arabia, in managing undergraduate medical education in response to the pandemic situation. We describe the process of implementing the curriculum's delivery online during the lockdown and the decisions regarding the final assessment for all years. Furthermore, we highlight the steps taken to prepare for the new academic year 2020-2021 as a blended learning approach in light of the COVID-19 situation.